The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/0004-6361/201527674
|View full text |Cite
|
Sign up to set email alerts
|

Giant molecular filaments in the Milky Way

Abstract: Context. Filamentary structures are common morphological features of the cold, molecular interstellar medium (ISM). Recent studies have discovered massive, hundred-parsec-scale filaments that may be connected to the large-scale, Galactic spiral arm structure. Addressing the nature of these giant molecular filaments (GMFs) requires a census of their occurrence and properties. Aims. We perform a systematic search of GMFs in the fourth Galactic quadrant and determine their basic physical properties. Methods. We i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 65 publications
4
86
0
1
Order By: Relevance
“…Ragan et al [62] found the kinematical distance in a plot of radial velocity vs. galactic longitude for many filaments to be in the interarm regions (seven filaments in their Figure 4). Abreu-Vicente et al [63] position about half of the filaments in the interarms (8 out of 17 in their Figure 1). For their GMF, their Table 2 and Section 3.1.1 gave different kinematic and extinction distances (about 3.4 kpc vs. about 4.9 kpc), or a difference about three times that of a typical arm width (≈ 0.6 kpc), making it difficult to say if a Giant Molecular Filament is located inside or outside an arm.…”
Section: Filamentsmentioning
confidence: 90%
“…Ragan et al [62] found the kinematical distance in a plot of radial velocity vs. galactic longitude for many filaments to be in the interarm regions (seven filaments in their Figure 4). Abreu-Vicente et al [63] position about half of the filaments in the interarms (8 out of 17 in their Figure 1). For their GMF, their Table 2 and Section 3.1.1 gave different kinematic and extinction distances (about 3.4 kpc vs. about 4.9 kpc), or a difference about three times that of a typical arm width (≈ 0.6 kpc), making it difficult to say if a Giant Molecular Filament is located inside or outside an arm.…”
Section: Filamentsmentioning
confidence: 90%
“…Filamentary structures are fundamental building blocks of the molecular clouds of the interstellar medium (ISM), manifesting themselves over wide ranges of sizes (∼0.1-100 pc), masses (∼1-10 5 M ⊙ ), and line-masses ( 1 000 M ⊙ pc −1 ) (e.g., Bally et al 1987;Hacar et al 2013;Alves de Oliveira et al 2014;Kainulainen et al 2013Kainulainen et al , 2016Abreu-Vicente et al 2016). Specifically, filaments that have line-masses greatly in excess to the critical value of the self-gravitating, thermally supported, non-magnetised, infinitely long equilibrium model, i.e., ≫16 M ⊙ pc −1 (Ostriker 1964), contain large enough mass reservoirs to give birth to high-mass stars and star clusters (e.g., Pillai et al 2006;Beuther et al 2010Beuther et al , 2015aHenning et al 2010;Schneider et al 2012;Kainulainen et al 2013;Stutz & Gould 2016;Contreras et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These surveys enable investigations of not only individual local phenomena such as stars, clusters, ionized gas and molecular or atomic clouds, but studies of our Galaxy as a whole, and we can compare the results to extragalactic studies (see, e.g., Taylor et al 2003;Churchwell et al 2009;Carey et al 2009;Schuller et al 2009;Anderson et al 2011;Walsh et al 2011;Beuther et al 2012;Ragan et al 2014;Wang et al 2015;Goodman et al 2014;Reid et al 2014;Abreu-Vicente et al 2016). Particularly important for a general understanding of the different physical processes is the multiwavelength approach because different surveys trace different components of the interstellar medium (ISM) and stellar populations, as well as varying temperature regimes and physical processes.…”
Section: Introductionmentioning
confidence: 99%